Optimizing the Utilization of Gadung Tubers (Dioscorea Hispida) as a Botanical Insecticide Based on Local Potential to Support Environmentally Friendly Agriculture in Pandan Wangi Village - Hadiatul Martini; Sitti Rohmi Djalilah; Khadafi Sani; Rida Mardatilah; Baiq Aryani Novianti; Fartina; Khaerus Syahidi (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
This community service program aimed to optimize the utilization of gadung tubers (Dioscorea hispida) as a botanical pesticide through a participatory community empowerment approach in Pandan Wangi Village, East Lombok Regency. The program involved three farmer groups and was implemented through demonstration, discussion, and hands-on practice. Program evaluation was conducted through participatory observation, discussions, documentation, and question-and-answer sessions, while the collected data were analyzed descriptively using a qualitative approach. The results showed that the participants understood the process of preparing and applying the botanical pesticide, as demonstrated by their ability to explain the preparation procedures, the functions of each material, and the application techniques during the evaluation sessions. Participants also showed positive responses toward the utilization of local resources as an environmentally friendly alternative for pest management and actively participated throughout the program. In addition, the program successfully produced a botanical pesticide derived from gadung tubers as one of its outputs. These findings indicate that optimizing local resources through a participatory approach effectively improves community knowledge and practical skills while fostering greater awareness of utilizing local potential to support environmentally friendly and sustainable agriculture